EFEKTIFITAS SOSIALISASI KEBIJAKAN PEMERINTAH KOTA BANDAR LAMPUNG TENTANG WAKTU PEMBUANGAN SAMPAH SEBAGAI UPAYA MENCIPTAKAN KEBERSIHAN LINGKUNGAN - Sentosa, Amalia Rusmaliana; Rochana, Erna (JURNAL SOSIOLOGI, 2012)
Government of Bandar Lampung in creating urban environmental hygiene makes a policy on waste disposal time at 22:00 to 5:30 pm. To achieve Government policy seeks Bandar Lampung socialize, socialization directly by the Government of Bandar Lampung is coordinated by the Department of Hygiene and Bandar Lampung, the implementation involves district and village officials, while media socialization through the installation of banners in the streets of the protocol . Regarding the results of socialization is not yet effective in fostering cleanliness of Bandar Lampung. It can be seen from the number of people who do not comply with the policy, resulting in still garbage strewn morning.Â Keywords: Â effectiveness, socialization, garbage disposal, environmental cleanliness